Comparação da qualidade de vida e sobrecarga dos cuidadores de pacientes com epilepsia por esclerose mesial temporal e epilepsia mioclônica juvenil - Westphal, Ana Carolina [UNIFESP] (2005)
INTRODUCTION: The relationship pattern between patient and caregiver can influence in quality of life (QOL) and growth of both. OBJECTIVE: To compare QOL and burden over the caregivers of patients with refractory temporal lobe epilepsy (TLE) due to mesial temporal sclerosis and juvenile myoclonic epilepsy (JME). CASUISTIC AND METHODS: 20 caregivers of patients with TLE and 20 of patients with JME were evaluated. The QOL Inventory SF-36 and the Caregiver Burden Questionnaire Burden Interview - Zarit - were applied. RESULTS: When QOL of both groups was compared, no relation statistically significant was observed between caregivers for JME and TLE, as well as burden on them. There was a correlation for burden on the caregivers of JME patients and the following domains of SF-36: General Health Status (p = 0.011), Emotional Limitation Aspects (p = 0.037) e Mental Health (p = 0.002). CONCLUSION: The burden on the caregivers of both groups was similar and did not interfere in QOL in most of SF-36 domains. However, caregivers of patients with JME suffered greater impact in domains related to physical and emotional health. In spite of more adequate seizure control in JME patients this burden might be heavier due to greater exposure to daily activities.